2016
DOI: 10.1037/neu0000249
|View full text |Cite
|
Sign up to set email alerts
|

Sending your grandparents to university increases cognitive reserve: The Tasmanian Healthy Brain Project.

Abstract: Results Growth Mixture Modelling demonstrated that 44.3% of the control sample showed no change in CR whereas 92.5% further education participants displayed a significant linear increase in CR over the 4 years of the study. These results indicate that older adults engaging in high level mental stimulation display an increase in CR over a 4 year period.Conclusions Increasing mental activity in older adulthood may be a viable strategy to improve cognitive function and offset cognitive decline associated with nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Specifically, we suggest that patients with low cognitive reserve may achieve greater cognitive improvements from interventions that strengthen functional processes (Figure 4, top chart), whereas patients with high cognitive reserve may achieve greater cognitive improvements from multimodal programmes that primarily focus on interventions promoting structural restoration (Figure 4, bottom chart), even if both groups of participants obtain greater benefits from multimodal programmes than from any single interventional approach. Therefore, if the implementation of the mentioned interventions during advanced stages of life promotes brain plasticity mechanisms similar to positive life experiences (Lenehan et al, 2016), then brain connectivity patterns will be optimized in a similar manner (Steffener and Stern, 2012;Marques et al, 2016), subsequently improving cognitive function. Factors related to cognitive training, such as learning a second language, have exhibited greater utility in preserving brain functioning in elderly subjects with low cognitive reserve than in subjects with high cognitive reserve (Alladi et al, 2013;Chertkow et al, 2010;Gollan et al, 2011), illustrating the greater benefits of functional interventions in subjects with low cognitive reserve than in subjects with high cognitive reserve.…”
Section: A Rationale For Weighting the Subcomponents Of Multimodal Prmentioning
confidence: 99%
“…Specifically, we suggest that patients with low cognitive reserve may achieve greater cognitive improvements from interventions that strengthen functional processes (Figure 4, top chart), whereas patients with high cognitive reserve may achieve greater cognitive improvements from multimodal programmes that primarily focus on interventions promoting structural restoration (Figure 4, bottom chart), even if both groups of participants obtain greater benefits from multimodal programmes than from any single interventional approach. Therefore, if the implementation of the mentioned interventions during advanced stages of life promotes brain plasticity mechanisms similar to positive life experiences (Lenehan et al, 2016), then brain connectivity patterns will be optimized in a similar manner (Steffener and Stern, 2012;Marques et al, 2016), subsequently improving cognitive function. Factors related to cognitive training, such as learning a second language, have exhibited greater utility in preserving brain functioning in elderly subjects with low cognitive reserve than in subjects with high cognitive reserve (Alladi et al, 2013;Chertkow et al, 2010;Gollan et al, 2011), illustrating the greater benefits of functional interventions in subjects with low cognitive reserve than in subjects with high cognitive reserve.…”
Section: A Rationale For Weighting the Subcomponents Of Multimodal Prmentioning
confidence: 99%
“…The Tasmanian Healthy Brain Project (THBP) is designed to assess the impact of university-level education on CR and cognitive function in healthy older adults [24] . We have recently demonstrated that further education leads to a measurable increase in current CR among older adults who undertake further education [25] . The aim of the present article was to examine if the observed increase in CR among older adults undertaking further education is associated with a change in cognitive function over time.…”
Section: Introductionmentioning
confidence: 96%
“…However, research on the potential protective effects of later‐life cognitive engagement and enrichment is limited. The Tasmanian Healthy Brain Project (THBP; Summers et al, 2013) has produced the first research on the potential benefit of formal late‐life education on cognitive reserve (Lenehan et al, ). However, investigation of later‐life EE in animal models of neuropathology has been limited.…”
Section: Introductionmentioning
confidence: 99%